2020
DOI: 10.1159/000510265
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of Juvenile Xanthogranuloma

Abstract: <b><i>Background:</i></b> Dermoscopy is useful for the evaluation of juvenile xanthogranuloma (JXG). The classical “setting sun” pattern is characteristic of JXG, but its sensibility appears to be limited. An extensive description of other dermoscopic findings is not available in the literature. <b><i>Objectives:</i></b> The aim of this study was to valuate and describe the clinical and dermoscopic characteristics of a series of JXG cases. <b><i>Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…4 Most common dermatoscopic feature seen in our series was yellow-white/yellowish-brown structureless areas (94%). This is in contrast to the report by Peruilh-Bagolini et al, 2 where the prominent background colour reported was pink-red or yellowish-orange. Three different pigmentary patterns were seen including perilesional, perifollicular and accentuated reticular/ pseudo-reticular network.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…4 Most common dermatoscopic feature seen in our series was yellow-white/yellowish-brown structureless areas (94%). This is in contrast to the report by Peruilh-Bagolini et al, 2 where the prominent background colour reported was pink-red or yellowish-orange. Three different pigmentary patterns were seen including perilesional, perifollicular and accentuated reticular/ pseudo-reticular network.…”
contrasting
confidence: 99%
“…However, unlike the previous studies, prominent basal layer pigmentation was not limited to late stages and was appreciable in early stages also. [1][2][3] Immunochemistry in all of the cases revealed CD68 positivity while CD1a and Langerin (CD207) was negative confirming diagnosis of JXG.…”
mentioning
confidence: 90%
“…JXG has a classic clinical appearance, presenting as a yellowish papule, often involving the head and neck, torso, or extremities 3 . Dermoscopy can be helpful as lesions classically demonstrate a “setting sun” pattern with additional findings of global symmetry, yellow globules, shiny white streaks, and irregular distribution of vascular structures 4 …”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Dermoscopic features of the entities that may clinically resemble cutaneous mastocytosis. References [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%